Improvement of crystalline quality of N-polar green InGaN/GaN multiple quantum wells on vicinal substrate. (15th June 2019) - Du, Jinjuan; Xu, Shengrui; Lin, Zhiyu; Zhang, Yachao; Zhang, Jincheng; Zhao, Ying; Peng, Ruoshi; Fan, Xiaomeng; Niu, Mutong; Huang, Jun; Hao, Yue
Abstract: The surface morphology, crystalline quality and optical characteristics of N-polar InGaN/GaN multiple quantum wells (MQWs) structures with emission in the green spectral range grown on planar and vicinal substrates were researched. The polarity of the samples was ascertained by convergent beam electron diffraction pattern. Scanning electron microscopy, high-resolution x-ray diffraction, cathodoluminescence, photoluminescence and Raman measurements demonstrated that MQWs structures on vicinal substrate had a smooth surface, better crystal quality, stronger luminescence intensity and less stress. Transmission electron microscopy illustrated that the structures on vicinal substrate could suppress the formation of inversion domains and the propagation of dislocations effectively.